Modernizing Higher Education in India: Quality Dimensions for Sustainable and Impactful Education - Rahmiaty Rahmiaty; Kamarullah Kamarullah; Fadhlur Rahman; Muhammad Haekal; Windia Hadi (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
The perspectives of international students on higher education institutions in India, especially in comparison to those in other developing countries, remain a critical concern, particularly when considering the highly competitive climate of studying abroad. This study seeks to examine the quality dimensions and facilities offered at a public university in Hyderabad, India, from the viewpoint of international students. This research fills an important gap by exploring what international students experience and expect during an increasingly competitive global academic system. A descriptive qualitative design was employed, to investigate the experiences of 120 international students from diverse academic disciplines and degree programs. Data were collected through questionnaires and in-depth interviews, with responses analyzed using descriptive statistical methods. Findings suggest that while international students generally view the institution’s quality services and facilities as comparable to global standards, they also express significant concerns, particularly with the ICT infrastructure, accessibility to laboratory practicums, and hygiene standards. Despite these challenges, the positive assessment of the institution’s quality services indicates areas for potential improvement, especially in instructional quality, teaching-learning processes, and examination mechanisms. Nonetheless, the study’s limitations include the potential for bias in self-reported data and limited generalizability outside similar socio-cultural and educational contexts. Future research should expand the sample size, employ longitudinal designs, and explore additional contextual factors to deepen understanding of international student satisfaction and develop sustainable improvement strategies for higher education quality.